PRELIMINARY STUDY OF THE DIALECTS OF KAMBERA - Raynesta Mikaela Indri Malo (Universitas Warmadewa, 2021)
Kambera language is a regional language used by speakers who live in the eastern part of the island of Sumba, in this case, East Sumba Regency. In previous studies, the claim stated by the researchers is that there is only 1 language spoken in East Sumba. However, the people of East Sumba, as native speakers, claim that there are several languages ​​used depending on the villages. This study aims to map these languages/dialects. This descriptive preliminary study is limited to make an inventory of basic vocabulary between 11 different locations determined based on the number of paraingu namely kabihu unions or ethnic clans in the past. The basic vocabularies are taken from Sawdesh 200-list and Leipzig-Jakarta 100-list. The combination of these lists results in 223 basic vocabularies which become the main data for this study. The data were collected through recording and note-taking.